International Courts and Their Contribution to Justice in the Context of the War in Ukraine - Rega, Iurii; Mernyk, Anastasiia; Adamovych, Oksana; Melnychuk, Olha; Chobotar, Dmytro (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Ensuring justice during the ongoing war in Ukraine represents one of the most pressing challenges for contemporary international law. This study examines the pivotal role of international judicial institutions—particularly the International Criminal Court (ICC), the European Court of Human Rights (ECHR), and various ad hoc tribunals—in enforcing accountability for war crimes, upholding human rights, and preserving the rule of law amid armed conflict. Using a qualitative research method, the study relies on comparative analysis as well as historical and legal approaches to understand how these institutions function within complex geopolitical contexts. Through qualitative data collection and interpretive analysis of court decisions, international conventions, and reports from global organizations, the research identifies structural and procedural challenges faced by international courts, including political interference, difficulties in gathering evidence, and limited coordination with domestic jurisdictions. Moreover, the study explores the role of international cooperation and judicial precedents in building a more consistent and enforceable global justice system. The findings suggest that while international courts play a critical role in prosecuting war crimes and deterring future violations, their effectiveness is often constrained by issues of state sovereignty and the lack of uniform enforcement mechanisms. Therefore, the paper argues for a strategic consolidation between international and national legal systems to ensure that justice is not only pursued but also realized in practice. Ultimately, this research contributes to the broader discourse on strengthening international criminal justice in the era of hybrid conflicts and global political polarization.